Flow injection amperometric evaluation of antioxidant capacity of chocolates having different cocoa content at a boron-doped diamond electrode - Arbneshi, Tahir; Frangu, Arber; Frühbauerová, Michaela; Červenka, Libor; Berisha, Liridon; Kalcher, Kurt; Sýs, Milan (My University, 2021)
Research background. The objective of this paper is to introduce an instrumentally simple analytical tool for determination of cocoa solids content in chocolates. This electroanalytical method is based on amperometric oxidation of all present antioxidants in chocolates at boron-doped diamond electrode (BDDE) that is integrated in a flow injection analysis (FIA) wall-jet electrode system. Experimental approach. As part of optimisation, thirteen commonly occurring antioxidants were investigated using cyclic voltammetry at BDDE in 0.1 mol/L phosphate buffer with different methanol (MEOH) content. Working parameters, such as of MeOH content, flow rate, and detection potential, were optimised. Principally, the height of the oxidation peak (current response) representing the oxidation of the sum of antioxidants (Total Antioxidant Content; TAC) was expressed as Trolox content. Results and conclusions. For analytical purpose, a linear range from 5.0 to 100 mg/L Trolox described by regression equation and characterized by correlation of determination 0.9994 was found. Obtained high positive correlation between determined values of Trolox equivalent antioxidant capacity (TEAC) and cocoa contents characterised by correlation coefficient of 0.9187 for eight randomly selected samples (one white, two milk, and five dark chocolates) confirmed the fact that cocoa solids represent the main source of antioxidants (reducing agents). Novelty and scientific contribution. The research demonstrates that TEAC values could be probably considered as additional marker of cocoa content in the chocolate analysis to commonly used theobromine (authenticity of food products). The developed FIA method could therefore serve as simple analytical tools in the food quality control.
Průtokové injekční amperometrické hodnocení antioxidační kapacity čokolád s různým obsahem kakaa na diamantové elektrodě dopované bórem
Keywords: Trolox equivalent antioxidant capacity; amperometry; boron-doped diamond electrode; flow injection analysis; cocoa content in chocolate; antioxidační kapacita ekvivalentní Troloxu; amperometrie; diamantová elektroda dopovaná bórem; průtoková injekční analýza; obsah kakaa v čokoládě